(untitled) (Economics and region, 2019)
The article explores the term “identity” and in particular “corporate identity”, which means the employees’ awareness of the organization’s value, their place in it, the creation of the “we” sense and the pride of affiliation to their organization. It is proved that among the basic elements of corporate identity the visual ones – symbols, signs, corporate color and font, form and composition – play the main role. This is because of the subconscious perception of visual information, and therefore, a greater emotional reaction. Due to the knowledge of the psychological peculiarities of perception in design and the ability to synthesize them into a single whole, it is possible to significantly improve the quality of a corporate style creation withing the organization.